A Literature Review of Maathulai Oaddu Choorna for Kalichal in Siddha Medicine (International Journal of Ayurveda and Pharma Research, 2025)
Four systems of traditional medicine have been adopted in Sri Lanka; Ayurveda, Siddha, Unani and Deshiya Chikitsa. The Siddha system of medicine is a traditional medical system that uses a scientific and holistic approach to provide preventive, promotive, curative, rejuvenating and rehabilitative healthcare. ‘Maathulai oaddu Choorna’ (MC) is of the internal medicine which is the poly herbal formulation. Maathulai oaddu Choorna is one of the most important drugs in Siddha Ayurvedha Government hospitals in Sri Lanka. Therefore, we selected this drug to literature review related its ingredients for ‘Kalichal’. Data for this review on 14 ingredients from 8 families were collected from relevant books, peer review journals and websites from October to December 2024. The characteristics of the ingredients that were identified for the review were plant morphology, parts used, Principal properties of each ingredient such as taste, potency and biotransformation, pharmacological actions, phytochemicals and medicinal uses. Among these ingredients, all were identified as herbal materials and 2 (14%) of species were found in Poaceae, Zingiberaceae, Lauraceae and Umbelliferae families. Based on the plant morphology 5 (35%) and 4 (28%) plants were herbs and trees respectively. 5 (35%) species were used as dry fruits. Among these ingredients 10 (71.4%) were pungent in taste, 8 (57.14%) were hot potency and 11 (78.5%) were pungent Vipaka. Pharmacological actions such as stomachic 10 (71.42%), carminative 9 (64.28%) and stimulant 8 (57.14%). Phytochemicals such as tannin 9 (64.28%) and volatile oil 8 (57.14%) were highly found in these ingredients. This literature review provides useful documentary evidences related its ingredients for Kalichal. There is need further extensive scientific studies should be carried out to justify in future.